Cost Modeling and Risk and Benefit Modeling Approach as a Tools For Decision Making in Adoption Cloud Computing as IT Strategic Business - Rian Rahmanda Putra; Wanda Kinasih; Dana Indra Sensuse (Computer Engineering and Applications Journal, 2014)
Cloud computing is an innovation that allows the use of IT as a utility based on-demand. Since cloud computing is a new technology, its led to a variety of risks that required an assessment model to assess the organization's readiness to adopt cloud computing. Moreover, by using cloud computing services means organizations or outsourcing involves a third party. Before adopting cloud computing technology, organizations need to consider some of the effects that arise as a result of cloud computing, namely in terms of costs, risks and benefits. To assist organizations to consider the migration of existing IT systems to the cloud, it can be used the cost approach valuation models and risk and benefit. This paper discusses two models of cost-based assessment of risk and benefit modeling and modeling that can be used as a tool to assist organizations in making decisions related to the migration of existing IT systems to the cloud. Â